Functional characterisation of cancer-associated fibroblasts from nasopharyngeal carcinoma / Wong Wee Lin - Wong, Wee Lin (2020)
Nasopharyngeal carcinoma (NPC) remains a major health issue in Southern China and Southeast Asia where the disease is endemic. Whilst the cure rate for early stage NPC is high, patients often present with late stage diseases and have a 5-year survival rate of less than 50%. NPC patients often suffer from severe treatment side effects because of the location of the tumours that is in proximity to various important organs in the head and neck region. Therefore, alternative therapeutic approaches are needed to improve the treatment outcomes and reduce patient morbidity. Targeted therapies are not in routine use to treat NPC and therapeutic advances will require a more detailed understanding of the molecular basis of the disease. The tumour microenvironment (TME), which consists of various non-malignant cell types and extracellular matrix proteins, is known to support tumour development and progression in a number of cancer types. Cancer-associated fibroblasts (CAFs) are often the pre-eminent cell type within the TME of solid tumours and a number of tumour promoting properties of CAFs have been described. The role of CAFs in the pathogenesis of NPC, however, has received little attention. The present study was designed to phenotypically characterise a panel of CAFs derived from NPC tumours (NPC-CAFs) by examining their expression of CAF markers (α-SMA, PDPN, FAPα, PDGFRα/β and CAV-1), degree of senescence as well as to investigate their functional roles in NPC pathogenesis. The present study showed that the CAF strains expressed heterogeneous levels of alpha-smooth muscle actin (α-SMA), and interestingly, the CAF strains with high levels α-SMA also contained a high proportion of senescent cells. Notably, NPC-CAFs exclusively expressed podoplanin (PDPN), as PDPN expression was absent in normal fibroblasts. Next, the ability of the CAFs to promote NPC cell proliferation and migration, and also inhibit EBV-specific CD8 T cell responses iv was investigated. MTT cell proliferation assays showed that conditioned media (CM) from NPC-CAFs had no effect in NPC cell proliferation. However, in transwell migration and T cell activation assays, CM from NPC-CAFs significantly enhanced the migration of NPC cells and inhibited IFN-γ production from antigen-stimulated EBV-specific CD8 T cells. Significantly, NPC-CAFs also inhibited CD8 T cells through cell-cell contact and this effect was likely to be PD-1/PD-L1 independent, as PD-L1 mRNA expression was not consistently upregulated in these NPC-CAFs. To begin to investigate which secreted proteins in the CM might be responsible for the effects on NPC cell migration and T cell activity, cytokine arrays were used to compare the profiles of cytokines secreted by normal fibroblasts and NPC-CAFs. The analyses revealed that NPC-CAFs had higher secretion of RANTES, MCP-3 and VEGF A than NPC-CAFs normal fibroblasts. Collectively, the present study showed that NPC-CAFs are phenotypically distinct from normal fibroblasts and may contribute to NPC pathogenesis by promoting a more motile and possibly metastatic phenotype in NPC cells, as well as by contributing to an immunosuppressive microenvironment. Therefore, the development of strategies to target CAFs could provide novel therapeutic opportunities for patients with NPC.